Respuesta :
Step-by-step explanation:
We have (x + y)² = (x + y)(x + y) = x² + 2xy + y².
Let x be 3a and y be 2.5b.
Therefore (3a + 2.5b)²
= (3a)² + 2(3a)(2.5b) + (2.5b)²
= 9a² + 15ab + 6.25b².
Hence the '*' sign should be replaced with 15ab.
Answer:
Given that, ( 3a + 2.5b )² = 9a² + 6.25b² + *
We know that, ( x + y )² = x² + y² + 2xy
According to the above problem, we get
( 3a + 2.5b )² = (3a)² + (2.5b)² + (2×3a×2.5b)
( 3a + 2.5b )² = 9a² + 6.25b² + 15ab
Therefore,
The sign " * " should be 15ab.
- 15ab is the right answer.